2022
DOI: 10.1071/sh21193
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive norms about condom use predict odds of using a condom during last sexual experience in a large, national survey of adolescents from Australia

Abstract: Background Reducing sexually transmitted infections among adolescents is an important public health goal in Australia and worldwide. This study estimated the association between condom use during last heterosexual sexual experience with two descriptive norms among a large, national sample of secondary school students from Australia. Methods A large, national online survey of 14- to 18-year-olds in Australia was conducted in 2018; a sub-analysis of sexually active participants (n = 2989) used multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…: Data included those from male (N = 414. It was also higher than another study, from Australia, which reported that 56% of adolescents had used a condom during their latest act of intercourse (12) national sample of secondary school students from Australia. Methods A large, national online survey of 14-to 18-year-olds in Australia was conducted in 2018; a sub-analysis of sexually active participants (n = 2989.…”
Section: Discussionmentioning
confidence: 57%
“…: Data included those from male (N = 414. It was also higher than another study, from Australia, which reported that 56% of adolescents had used a condom during their latest act of intercourse (12) national sample of secondary school students from Australia. Methods A large, national online survey of 14-to 18-year-olds in Australia was conducted in 2018; a sub-analysis of sexually active participants (n = 2989.…”
Section: Discussionmentioning
confidence: 57%
“…= 1. 19) and there were 108 (6.1%) young people who reported that their first sexual experience had occurred when they were younger than 14 years. The average number of sexual partners With respect to their most recent (or only) sexual encounter, 51.2% (n = 926) reported they had used a condom.…”
Section: Condom Use For Past Sexual Experiencesmentioning
confidence: 99%
“…Many young people do not believe condom use is common among their peer group and are less likely to use condoms regularly as a result. [15][16][17][18][19][20] In this paper, we report findings from the 2021 iteration of a large, periodic survey of school-aged young people in Australia (14-18 years), the Secondary Students and Sexual Health (SSASH) survey. 15 While a quantitative survey offers only limited insight into the nuance of condom use as it relates to contemporary sexual cultures, our aim was to explore condom use in the context of young people's sexual and relationship experiences.…”
Section: Introductionmentioning
confidence: 99%